Dédicaces dans le Romant satyrique (1624) et dans le Romant des Indes (1625) de Jean de Lannel : un cas de complexe de Pygmalion ? - Frédéric Briot (Les Dossiers du GRIHL)
Le Romant satyrique (1624) and Le Romant des Indes (1625), by Jean de Lannel, look very similar. According to A. Maynor Hardee (Droz, 1967, p. 23-24), “Lannel changed most of the names to sound more Indian, added one secondary episode and substitute another, revisions that in no way obviate recognition of the same historical background and events”. Yet one may see some obvious and racy alteration in all the margins: title, adress to the reader, dedicatory epistle, privilege. Can those political margins alter the meaning of the novel? Do we face twice the same novel, or two separate novels? Or even more?